30 Does the heart score predict outcomes of chest pain admissions and can it facilitate a safe early discharge?. (28th September 2016) - Bajrangee, A; Mahabir, S; Flood, R; Tierney, A; Coughlan, JJ; Ullah, I; Sullivan, V; Maree, AO
Abstract : Aim: The focus of the diagnostic process in chest pain presentations to the accident and emergency department is to rapidly identify low and high-risk patients for acute coronary syndromes (ACS). The HEART score facilitates this but we sought to determine its utility in safely discharging patients. Methods: In this prospective observational study consecutive patients presenting to St James Hospital with chest pain, without ST elevation between January – July 2015 were followed. The primary outcome was to determine if the HEART score was predictive of six-week major adverse cardiovascular event (MACE) defined as the composite incidence of myocardial infarction, stroke, unplanned revascularisation and death. Baseline demographics, clinical diagnosis and traditional cardiac risk factors, troponin level, ischaemic electrocardiogram changes, HEART score (1–10), admission rates, plaque burden (Syntax and GENSINI score) and MACE at six weeks were recorded. Results: One hundred and twenty four patients, 43 with a diagnosis of non-cardiac chest pain (NCCP), 44 with stable angina (SA) and 37 with unstable angina (UA) were followed. Table 1 illustrates patient characteristics. Data is presented as mean and standard deviations for continuous data and as percentages for dichotomous data. The six-week incidence of MACE was 3.7% for a HEART score of 0–3, 54% for a HEART score of 4–6 and 73% for a HEART score of 7–10 (p < 0.0001). The HEART score accurately predicted the incidence of MACE at six weeks in all groups with an area under the curve of 0.96 (95% CI: 0.93−0.98, p < 0.001). The HEART score correlated with total plaque burden measured by GENSINI score r = 0.4 (p < 0.001) and Syntax score r = 0.3 (p = 0.003). 44% of patients had a HEART score of 0–3 of which could have facilitated a safe early discharge for this cohort. Conclusion: The HEART score is an effective tool for safely identifying chest pain patients at high risk of MACE. Its application can facilitate safe early discharge for low risk patients.